The Effect of Customer Experience, Product Variation and Customer Satisfaction on Customer Loyalty in Islamic Business Perspective (Study on Customer of PT. Pegadaian CP Tanjung Karang Center) - Lilis Jayanti; Zulaikah; Yeni Susanti (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the effect of customer experience, product variation and customer satisfaction on customer loyalty at PT. Pegadaian CP Tanjung Karang Center. This type of research is a quantitative research with descriptive and associative approach. In this study the population used is the customer of PT. Pegadaian CP Tanjung Karang Center. Determination of the sample size is based on the calculation of the slovin method, then the number of samples in this study is 100 respondents. The data collection technique of this study is spread questionnaire. Data analysis tools used in this study using SPSS 25. The results of the study explain that customer experience has a positive and significant effect on customer loyalty. Good experience, honesty, and fairness in Islamic business is able to increase trust and loyalty. Product variations also have a positive and significant effect on loyalty, because they are able to meet the needs of various customers. Customer satisfaction shows a positive and significant influence on loyalty satisfied customers will tend to remain loyal and have ongoing confidence in PT. Pegadaian services. Simultaneously, the three variables together affect customer loyalty positively and significantly. In the Islamic business perspective, transparency, honesty, and trustworthiness are the basis for creating customer satisfaction and loyalty, as well as supporting business sustainability, increasing the trust of the PT. Pegadaian community.